Interobserver Agreement of The Sonographic Evaluation for Fetal Biometry Among Normal and Obese Mothers: Sonographic Evaluation for Fetal Biometry Among Normal and Obese Mothers - Saleem, Muhammad Adeel; Bacha, Raham; Fatima, Hamnah; Fatima, Mehreen; Raheel, Muhammad; Taj, Zareen; Manzoor, Iqra (Pakistan BioMedical Journal, 2022)
Obesity is a disease and acts to develop myriad of clinical condition. Along with causing other diseases it renders difficulties in some physical and imaging examination of obese patients as a challenge. Therefore, the consistency of results has a great deal of variation for sonographer. Objective: Study was aimed to evaluate the interobserver agreement in the fetal biometry among normal and obese mothers. Methods: The study includes obese and normal pregnant females with single alive without any anomaly or growth retardation fetus. Low frequency convex array transducer is used. Total 140 Patients were included and categorized according to BMI. Inter item correlation, ICC and CRC were calculated for all variables. Bland-Altman plots were constructed. T-test was applied p-value 0.05 considered significant. Results: It was observed that the variation in normal and obese pregnant ladies in third trimester is not significant and a strong agreement between the observers in both normal and obese. Conclusion: Obesity causes many problems in sonographic fetal biometry. It was observed that the variation in normal and obese pregnant ladies in third trimester is not significant and a strong agreement between the observers in both normal and obese categories.